Expeditions around Stalin’s prison camps: from Yakutsk to Magadan - Kradin, Nikolai (project baikal, 2021)
The article presents the materials of seven expeditions made by the author and his fellow architects from 2012 to 2021 around Stalin’s prison camps located in the territory from Yakutsk to Magadan. Researchers performed photographic record of the remains of camp buildings of various types and wooden bridges with unique design, described mines where prisoners mined tungsten and other minerals essential to the defense of the country. The article presents measurements of bridges, camp buildings, civil objects and author's photographs of the given objects.
Keywords: Stalinism; repression; Black Clamp; bridges; Hare loop; the Alaskite mine; Butugychag; Seimchan